2022
DOI: 10.1002/adma.202203518
|View full text |Cite
|
Sign up to set email alerts
|

Transformable ECM Deprivation System Effectively Suppresses Renal Cell Carcinoma by Reversing Anoikis Resistance and Increasing Chemotherapy Sensitivity

Abstract: Extracellular matrix (ECM) is crucial in various biological functions during tumor progression, including induction of anoikis resistance and cell adhesion‐mediated drug resistance (CAM‐DR). Fibronectin (FN) is a vital ECM component with direct regulatory effects on ECM‐mediated anoikis resistance and CAM‐DR, making it an attractive and innovative therapeutic target for depriving ECM in tumor tissue. Herein, an ECM deprivation system (EDS) is developed based on FN targeting self‐assembly peptide for constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Extracellular matrix (ECM) is essential for various biological functions during tumor progression, including the induction of anoikis resistance and cell adhesion- mediated drug resistance ( Wang et al, 2022 ). Our data show significant differences in susceptibility to chemotherapeutic agents in different risk stratifications after risk modeling with anoikis-associated genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular matrix (ECM) is essential for various biological functions during tumor progression, including the induction of anoikis resistance and cell adhesion- mediated drug resistance ( Wang et al, 2022 ). Our data show significant differences in susceptibility to chemotherapeutic agents in different risk stratifications after risk modeling with anoikis-associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Quinazolines trigger anoikis in RCC by targeting the focal adhesion survival signaling, resulting in potent antitumor effects ( Sakamoto et al, 2011 ). Recent studies have shown that the ECM deprivation system (EDS) based on Fibronectin (FN) -targeted self-assembling peptide can effectively inhibit renal cell carcinoma by reversing anoikis resistance ( Wang et al, 2022 ). However, there is no effective RCC risk prediction model based on anoikis to reflect the impact of anoikis-related genes on prognosis comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pathogenesis of AD is still unclear at present, which can affect and delay the diagnosis of AD; thus, it is necessary to nd indicators to ensure quick and accurate diagnosis of AD. Anoikis is a form of apoptosis induced by the detachment of anchorage-dependent cells from adjacent cells and/or surrounding matrix, which leads to their incompatibility with the microenvironment [16,17]. Anoikis resistance has been extensively studied in the eld of oncology due to the ability of invasive cancer cells to survive away from the primary site[18], while degradation of ECM components, oxidative stress, and apoptosis of smooth muscle cells are closely related to the functions of ARGs in the pathogenesis of AD, therefore, we speculated that certain ARGs might be early diagnostic indicators for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have elucidated the various mechanisms employed by cancer cells to eliminate anoikis and promote their metastasis and invasion. Therapeutic approaches targeting anoikis have been initiated in some cancers [21]. In studies on CRC, genes such as CPT1A, IF1 and KLF5 have been found to be involved in anoikis resistance [14,16,17].…”
Section: Discussionmentioning
confidence: 99%